2013
DOI: 10.4149/gpb_2013051
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of membrane-bound fatty acid desaturases

Abstract: Abstract. Membrane-bound desaturases play key role in metabolism of polyunsaturated fatty acids. Characterization of these enzymes and their genes is the first step in basic understanding of their proper functioning in living cells as well as in tailor-made preparation of highly-specific and highlyproductive strains of microorganisms interesting for applied biotechnology. It is also the crucial step in creation of transgenic agricultural crops with enhanced content of individual polyunsaturated fatty acids. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In plant cells, saturated fatty acids are synthesized by the type II fatty acid synthase system with the aid of an acyl carrier protein (ACP). The biosynthesis of unsaturated fatty acid is conducted by the desaturation of saturated fatty acids depending on two kinds of acyl lipases, which include glycerol-3-phosphateacyl transferase (GPAT) that is responsible for the lipidization on the C-1 position of the glycerol skeleton, and monoacyl-glycerol-3-phosphateacyl transferase (MGAT) that is responsible for the lipidization at the C-2 position, as well as various fatty acid desaturases (FAD) (Klempova et al, 2013). Acyl carrier protein is a small, acidic protein that plays an essential role in fatty acid synthesis by elongating fatty acid chains.…”
Section: Effects Of Cold Stress On Membrane Lipid Unsaturationmentioning
confidence: 99%
“…In plant cells, saturated fatty acids are synthesized by the type II fatty acid synthase system with the aid of an acyl carrier protein (ACP). The biosynthesis of unsaturated fatty acid is conducted by the desaturation of saturated fatty acids depending on two kinds of acyl lipases, which include glycerol-3-phosphateacyl transferase (GPAT) that is responsible for the lipidization on the C-1 position of the glycerol skeleton, and monoacyl-glycerol-3-phosphateacyl transferase (MGAT) that is responsible for the lipidization at the C-2 position, as well as various fatty acid desaturases (FAD) (Klempova et al, 2013). Acyl carrier protein is a small, acidic protein that plays an essential role in fatty acid synthesis by elongating fatty acid chains.…”
Section: Effects Of Cold Stress On Membrane Lipid Unsaturationmentioning
confidence: 99%
“…In the present study, we found that the expression levels of ∆9 and ∆15 desaturases were substantially increased, but ∆12 desaturases had no obvious change when F. graminearum was cultivated at 10 • C compared with that at 25 • C. ∆9 is the only desaturase existing in all types of organisms, which play an indispensable role in maintaining the appropriate fluidity of biofilms during evolution [17]. Compared with other fatty acid desaturases, the activity of ∆9 desaturases was mostly involved in changing the membrane fluidity during temperature variation [71,72].…”
Section: Discussionmentioning
confidence: 45%
“…Fatty acids are important components of biofilms, which are responsible for receiving signals from external environmental factors [17]. The changes in the physiological, biochemical and physical properties of the biofilm directly reflect the impact of the environment on organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Humans consume predominantly six common edible saturated FA, such as hexadecanoic acid (palmitic acid), (9Z)-hexadec-9-enoic acid (palmitoleic acid), octadecanoid acid (stearic acid, cetylacetic acid), cis-9-octadecenoic acid (oleic acid), linoleic acid (LA, cis, cis-9,12-octadecadienoic acid) and a-linolenic acid (ALA, (9Z,12Z,15Z)-octadeca-9,12,15-trienoic acid) [149,202,203].…”
Section: Disruption Of Lipid Metabolismmentioning
confidence: 99%
“…Fatty acid precursors such as ALA are converted to the more pro-inflammatory n-6 polyunsaturated fatty acid (omega-6-, x-6-PUFAs: C20H32O2, 20:4(x-6)), such as dihomo gamma-linolenic acid (DGLA), arachidonic acid (AA), docosatetranoic acid, (7Z,10Z,13Z,16Z)-7,10,13, 16docosatetraenoic acid (DTA) and osbond acid, (All-Z)-4,7,10,13,16-docosapentaenoic acid (BDPA), and through LA into the less inflammatory n-3 polyunsaturated fatty acids (omega-3-, x-3-PUFAs), such as eicosatetraenoic acid, all-cis-8,11,14,17-eicosatetraenoic acid (ETA), eicosapentaenoic acid, (5Z,8Z,11Z,14Z,17Z)-eicosa-5,8,11,14,17pentenoic acid (EPA), docosapentaenoic acid, 7,10,13,16, 19-docosapentaenoic acid (DPA) and docosahexaenoic acid, (4Z,7Z,10Z,13Z, 16Z,19Z)-docosa-4,7,10,13,16,19-hexaenoic acid (DHA). Key reaction in biosynthesis of PUFA is desaturation [203][204][205]. Enzymes transfer electrons from one molecule to another and desaturate the substrate by adding a double bond.…”
Section: Disruption Of Lipid Metabolismmentioning
confidence: 99%